ANALISIS PENGENDALIAN KUALITAS PROSES WIREBOND ALU PADA PT. XYZ BATAM - Audita S; Arsyad Sumantika (LPPM Universitas Putera Batam, 2025)
This study was conducted at PT. XYZ Batam to analyze defects in the aluminum wire bonding process using the Orthodyne 7200 machine. The objective is to identify the most frequent defects, determine their root causes, and provide improvement recommendations. The methodology applied includes Failure Mode and Effect Analysis (FMEA) to calculate the Risk Priority Number (RPN), and Fault Tree Analysis (FTA) to trace the root causes. The results indicate that defects such as Lifted Bond on Die and Non-Stick Wedge on Lead have the highest RPN scores. The main contributing factors are suboptimal machine parameters, including bonding pressure, temperature, and ultrasonic frequency. Recommended improvements focus on better parameter control and enhanced operator training. This study is expected to support the company’s goal of achieving through more effective process control.